Strategic Integration of Artificial Intelligence and FinTech Innovations in Renewable Energy Management - Alzaydi, Ammar; Abedalrhman, Kahtan (International Journal of Engineering and Management Research, 2024)
The intersection of Artificial Intelligence (AI) and Financial Technology (FinTech) with renewable energy heralds a transformative era in energy systems worldwide. This paper explores the pivotal role of these technologies in facilitating the efficient integration and management of renewable energy sources. As global energy paradigms shift towards sustainable models, the deployment of AI enhances predictive analytics, grid management, and energy storage systems, thereby optimizing the reliability and efficiency of renewable energy. Concurrently, FinTech innovations emerge as crucial enablers, offering novel funding mechanisms and investment frameworks through blockchain and smart contracts, which ensure transparent and efficient financial transactions in the energy sector. This paper provides a comprehensive review of current technologies, highlights key applications, and discusses the integration strategies of AI and FinTech that enhance the scalability and effectiveness of renewable energy solutions. Moreover, it addresses the regulatory and ethical considerations that accompany technological advancements, ensuring a balanced perspective on fostering innovation while mitigating risks. By presenting case studies and future predictions, the paper aims to underline the potential for AI and FinTech to revolutionize energy systems, setting a blueprint for stakeholders to navigate the complexities of renewable energy integration.